2011
DOI: 10.1111/j.1479-8301.2011.00354.x
|View full text |Cite
|
Sign up to set email alerts
|

Subjective experiences of family caregivers of patients with dementia as predictive factors of quality of life

Abstract: Background: The aim of the present study was to investigate predictive factors of quality of life (QOL) in home caregivers of patients with dementia. Methods: A total of 118 home caregivers (48 male, 70 female) were asked to complete the World Health Organization (WHO) Quality of Life 26 (WHO/ QOL-26) questionnaire, the Pines Burnout Measure (BM), and the Beck Depression Inventory, second edition (BDI-II). Patient demographics and clinical data regarding cognitive impairment, neuropsychiatric symptoms, and dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
47
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 23 publications
6
47
0
4
Order By: Relevance
“…These results corroborate the results in the literature, which stress the inverse association between caregiver burden 18,19 and depressive symptoms 20,21 and QoL of caregivers. It has been suggested that caregivers' subjective experiences of depression and burden were more predictive of caregivers' QoL than the objective PwD-related variables, such as the PwD cognitive impairment or functional abilities 20 . Although our study showed that the same factors were related to the QoL of the caregivers who cared for mild and moderate dementia, the associated factors differed according to the severity of the dementia.…”
Section: Discussionsupporting
confidence: 83%
“…These results corroborate the results in the literature, which stress the inverse association between caregiver burden 18,19 and depressive symptoms 20,21 and QoL of caregivers. It has been suggested that caregivers' subjective experiences of depression and burden were more predictive of caregivers' QoL than the objective PwD-related variables, such as the PwD cognitive impairment or functional abilities 20 . Although our study showed that the same factors were related to the QoL of the caregivers who cared for mild and moderate dementia, the associated factors differed according to the severity of the dementia.…”
Section: Discussionsupporting
confidence: 83%
“…Caregivers of persons with dementia had a higher level of unmet needs for formal services and faced more barriers in accessing services when compared to other caregivers of chronically ill patients (Harmell et al, 2011;Stirling et al, 2010). However, much of the research on dementia caregivers is centered on psychological well-being such as stress, depression, and anxiety (Brodaty & Donkin, 2009;Gaugler et al, 2008;Harmell et al, 2011, Takai et al, 2011. Although there is evidence to suggest that an increase in caregiver's mastery and self-efficacy leads to better coping, which in turn has a protective effect on their well-being (Harmell et al, 2011), few studies have explored what can be done to alleviate caregiver challenges in accessing and utilizing resources that have the potential to improve quality of life for both persons with dementia and their family caregivers.…”
mentioning
confidence: 99%
“…Members of the immediate family, such as spouses and/or adult children, often take on the responsibility of caring for a person with dementia (Alzheimer's Association, 2013a). Research suggests that caregivers often feel unprepared after a family member receives a diagnosis of dementia (Chenoweth & Spencer, 1986;Gibson & Anderson, 2011;Takai, et al, 2011). Additionally, family caregivers often struggle to understand the cognitive decline and associated behavioral changes of their loved one, often ascribe a negative meaning to their relative's behavior, and blame the person rather than the disease (Vernooij-Dassen, Draskovic, McCleery, & Downs, 2011).…”
mentioning
confidence: 99%
“…Recent research on caregivers of patients with dementia (Takai et al, 2011) suggests that the subjective experience of the caregiver may be more important than patient-related variables in determining caregiver quality of life. We found the subjective experience of most of our male caregivers to be one of isolation, despair, frustration, and imprisonment.…”
Section: Discussionmentioning
confidence: 99%